فیض احمد فیض کی شاعری میں انسانی حقوق کا تصور (Al-Aasar, 2026)
Although the concept of human rights has acquired a formal legal and international status in the modern world, its roots are deeply embedded in human consciousness, civilizational development, and literary expression. Urdu poetry—particularly the poetry of Faiz Ahmed Faiz—presents the idea of human rights not merely as a legal construct but as a living human experience. This study examines the lexical and intellectual dimensions of the notions of “right” and “human rights,” tracing their formation within diverse civilizational contexts. It further analyzes the poetry of Faiz Ahmed Faiz as a significant intellectual text to demonstrate how literature contributes to the formation, articulation, and expansion of human rights consciousness.